Over 20 MHz modulation bandwidth on 250 nm emission of AlGaN micro‐LEDs. Issue 4 (1st February 2015) - Akhter, M.; Pampili, P.; Zubialevich, V.Z.; Eason, C.; Quan, Z.H.; Maaskant, P.P.; Parbrook, P.J.; Corbett, B.
Abstract : Bandwidth measurements of deep ultra‐violet micro‐light‐emitting diode (LED) electroluminescence centred at 250 nm using a multiple quantum well aluminium gallium nitride (AlGaN)‐based LED structure grown on a sapphire substrate is presented. By controlled etching of the wafer surface, parabolically shaped micro‐LED structures were formed to enhance light emission through the substrate. Devices were tested on‐wafer and bandwidth measurements were carried out on individual emission peaks from the devices. A bandwidth of more than 20 MHz was achieved on the 250 nm peak.